Joint associations of insomnia and sleep duration with prevalent diabetes: The Hispanic Community Health Study/Study of Latinos (HCHS/SOL). (21st July 2015) - Cespedes, Elizabeth M.; Dudley, Katherine A.; Sotres‐Alvarez, Daniela; Zee, Phyllis C.; Daviglus, Martha L.; Shah, Neomi A.; Talavera, Gregory A.; Gallo, Linda C.; Mattei, Josiemer; Qi, Qibin; Ramos, Alberto R.; Schneiderman, Neil; et al.
Abstract: Background: Inadequate sleep quantity and quality are associated with a higher risk of type 2 diabetes. This relationship is not well‐examined in US Hispanics/Latinos, and prior analyses may be confounded by sleep apnea. This cross‐sectional study examined joint associations of sleep duration and insomnia with diabetes among diverse US Hispanic/Latinos. Methods: Baseline data on sleep quantity and quality were obtained from 15227 participants (mean age 41; range 18–74 years) from the Hispanic Community Health Study/Study of Latinos. Complex survey multinomial logistic regression was used to examine associations between prevalent diabetes and six phenotypes defined by cross‐classifying sleep duration (short ≤6 h, average >6–9 h, long >9 h) and insomnia, adjusting for sex, age, site and Hispanic/Latino background interaction, education, physical activity, diet quality, and sleep apnea. Results: In the weighted population, 14% had diabetes, 28% had insomnia, 9% were short sleepers, and 19% were long sleepers. Compared with those with average sleep and no insomnia, those with short sleep and insomnia were more likely to have diabetes (odds ratio [OR] 1.46; 95% confidence interval [CI] 1.02, 2.11). Average sleepers with insomnia (1.28; 95% CI 1.02, 1.61) and long sleepers without insomnia (1.33; 95% CI 1.07, 1.65) also had elevated odds of diabetes. Further adjustment for body mass index attenuated associations, except with long sleep without insomnia. Conclusions: Both decreased quantity and quality of sleep are associated with diabetes in Hispanic/Latinos, with the greatest odds among those with short sleep duration and insomnia. The association is largely explained by obesity.